THE INFLUENCE OF ORGANIZATIONAL CLIMATE AND ORGANIZATIONAL COMMITMENT TO TURNOVER INTENSION OF EMPLOYEES OF PT SALAH SATU BRANCH OF BANK BUMN - Ependi, Nur Haris; Purnomo, D; Siswandi, Siswandi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
The purpose of this study is to measure the impact of organizational commitment organizational climate on employee turnover intentions of one state-owned bank in Jakarta. The method used in this study is to use a quantitative descriptive analysis involving employees at one of the state-owned banks using random sampling technique with proportional random sampling as many as 78 respondents. The data collection technique used is the questionnaire method which is supported by the documentation method with multiple linear regression analysis techniques. The results of the study can be indicated (1) There is a significant positive effect between organizational climate on employee turnover intentions where the negative value is -0,177 and the results of the t test are -1,737 which means t arithmetic is less than t table (-1.737